NF-κB/p65 Competes With Peroxisome Proliferator-Activated Receptor Gamma for Transient Receptor Potential Channel 6 in Hypoxia-Induced Human Pulmonary Arterial Smooth Muscle Cells - Wang, Yan; Li, Naijian; Wang, Yingfeng; Zheng, Guobing; An, Jing; Liu, Chang; Wang, Yajie; Liu, Qicai (Frontiers in Cell and Developmental Biology, 2021)
Objective: Peroxisome proliferator-activated receptor gamma (PPARγ) has an anti-proliferation effect on pulmonary arterial smooth muscle cells (PASMCs) via the transient receptor potential channel (TRPC) and protects against pulmonary artery hypertension (PAH), whereas nuclear factor-kappa B (NF-κB) has pro-proliferation and pro-inflammation effects, which contributes to PAH. However, the association between them in PAH pathology remains unclear. Therefore, this study aimed to investigate this association and the mechanisms underlying TRPC1/6 signaling-mediated PAH. Methods: Human pulmonary arterial smooth muscle cells (hPASMCs) were transfected with p65 overexpressing (pcDNA-p65) and interfering plasmids (shp65) and incubated in normal and hypoxic conditions (4% O2 and 72 h). The effects of hypoxia and p65 expression on cell proliferation, invasion, apoptosis, [Ca2+]i, PPARγ, and TRPC1/6 expression were determined using Cell Counting Kit-8 (CCK-8), Transwell, Annexin V/PI, Fura-2/AM, and western blotting, respectively. In addition, the binding of p65 or PPARγ proteins to the TRPC6 promoter was validated using a dual-luciferase report assay, chromatin-immunoprecipitation-polymerase chain reaction (ChIP-PCR), and electrophoretic mobility shift assay (EMSA). Results: Hypoxia inhibited hPASMC apoptosis and promoted cell proliferation and invasion. Furthermore, it increased [Ca2+]i and the expression of TRPC1/6, p65, and Bcl-2 proteins. Moreover, pcDNA-p65 had similar effects on hypoxia treatment by increasing TRPC1/6 expression, [Ca2+]i, hPASMC proliferation, and invasion. The dual-luciferase report and ChIP-PCR assays revealed three p65 binding sites and two PPARγ binding sites on the promoter region of TRPC6. In addition, hypoxia treatment and shPPARγ promoted the binding of p65 to the TRPC6 promoter, whereas shp65 promoted the binding of PPARγ to the TRPC6 promoter. Conclusion: Competitive binding of NF-κB p65 and PPARγ to TRPC6 produced an anti-PAH effect.